2012
DOI: 10.1007/s00403-012-1209-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies of cell signaling in a reconstructed human epidermis exposed to sensitizers: IL-8 synthesis and release depend on EGFR activation

Abstract: Models of reconstructed human epidermis (RHE) holding proliferating and fully differentiated cultured keratinocytes allow in vitro investigation of early molecular and cellular epidermal events during the complex response of keratinocytes at the onset of allergic contact dermatitis (ACD) or sensitization. In this study, data collected on RHE exposed to well-characterized sensitizing chemicals, such as dinitrofluorobenzene, oxazolone, cinnamaldehyde and isoeugenol, revealed a transient expression of IL-8 mRNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…(Fig. 1 C ) It has been reported that nuclear factor-κB (NF-κB), p38 MAPK, and ERK are involved in IL-8 secretion of keratinocytes (22,23). Since we had previously demonstrated that upregulation of NF-κB and p38 MAPK was not observed in high glucose–cultivated keratinocytes (21), we focused on ERK signaling.…”
Section: Resultsmentioning
confidence: 98%
“…(Fig. 1 C ) It has been reported that nuclear factor-κB (NF-κB), p38 MAPK, and ERK are involved in IL-8 secretion of keratinocytes (22,23). Since we had previously demonstrated that upregulation of NF-κB and p38 MAPK was not observed in high glucose–cultivated keratinocytes (21), we focused on ERK signaling.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, it appears that epidermal keratinocytes challenged by various alterations in their environment behave in a similar manner and exhibit stimulation of their endogenous expression of HB-EGF. This is concomitant with stimulation of the expression of other gene products, such as interleukin-8 after cholesterol depletion (Mathay et al, 2011) or exposure to sensitizing chemicals (Frankart et al, 2012), matrix metalloproteases 1 and 10 (Mathay et al, 2011;Stoll et al, 2012), and even more surprisingly, involucrin (Mathay et al, 2008;Giltaire et al, 2009;Mathay et al, 2011). Now, Stoll et al (2012) reveal that keratinocytes overexpressing HB-EGF are very likely triggered toward a motile, abnormally differentiated, but also poorly proliferative, phenotype.…”
Section: Hb-egf Expression In Challenged Keratinocytesmentioning
confidence: 97%
“…IL-1α activates the p38 MAPK pathway to increase the expression of HSPB1, which causes anti-apoptotic effects, possesses chaperone-like activity and refolds denatured proteins, and is cytoprotective against heat shock [35]. EGFR also increases the expression of IL-8 [39] and plays an essential role in re-epithelialization by increasing keratinocyte proliferation and cell migration in wounded skin [40]. The constant gene expressions of EGFR and HSPB1 substantiate the absence of damage from fucoxanthin, but does not explain the reduction in IL-6 and IL-8 gene expression.…”
Section: Discussionmentioning
confidence: 99%